Recycling high purity silicon from solar grade silicon cutting slurry waste by carbothermic reduction in the electric arc furnace. (1st July 2019) - Liu, Yang; Kong, Jian; Zhuang, Yanxin; Xing, Pengfei; Yin, Huayi; Luo, Xuetao
Abstract: The complete separation of ultrafine silicon particles and silicon carbide (SiC) particles is very difficult, which is a great dilemma for recycling high purity kerf loss silicon (Sik ) from solar grade silicon cutting slurry waste (SoG-Siw ). Here, we report a novel carbothermic reduction process for obtaining high purity silicon from SoG-Siw . SoG-Siw was firstly purified by acid leaching, then cleaned with high purity water and pelleted with high purity silica sand. After refining in an electric arc furnace (50 kW), Sik and SiC particles were completely separated. The obtained silicon had the purity of 99.15 wt% and lower concentration of boron (B, 0.06 ppmw) and phosphorus (P, 0.24 ppmw), which had met the standard of B and P for solar cells. The overall yield of recycling silicon was 63%. The influence of iron, particle size of high purity silica sand and SiO2 :SiC ratio on the silicon recycling are investigated. In addition, the mechanism for the separation of Sik and SiC particles by the metallurgical process is analyzed. The reacted reactants with different states inside the crucibles are observed and the reaction process is analyzed. This metallurgical process overcomes the technical bottlenecks for the complete separation of Sik and SiC from SoG-Siw . Specially, this process can be scaled up for commercial production. Highlights: SiC particles were completely removed from the pure Si-SiC mixture by the reduction of SiC with SiO2 using a home-built EAF operated at high temperature. The influence of iron, particle size of high purity silica sand and SiO2 :SiC ratio on the silicon recycling are investigated. The mechanism for the separation of Sik and SiC particles by the metallurgical process is analyzed. The internal of graphite crucible after the metallurgical process without and with adding high purity silica sand are compared and the reaction process is analyzed. The process concurrently realizes the removal of SiC particles and the production of silicon with low boron and phosphorus.